Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences